Lignin Refinery Using Organosolv Process for Nanoporous Carbon Synthesis - Imam Prasetyo (Molecules, 2020)
Porous carbon has been widely used for many applications e.g., adsorbents, catalysts, catalyst supports, energy storage and gas storage due to its outstanding properties. In this paper, characteristics of porous carbon prepared by carbonization of lignin from various biomasses are presented. Various biomasses, i.e., mangosteen peel, corncob and coconut shell, were processed using ethanol as an organosolv solvent. The obtained lignin was characterized using a Fourier transform infrared (FTIR) spectrophotometer and a viscosimeter to investigate the success of extraction and lignin properties. The results showed that high temperature is favorable for the extraction of lignin using the organosolv process. The FTIR spectra show the success of lignin extraction using the organosolv process because of its similarity to the standard lignin spectra. The carbonization process of lignin was performed at 600 and 850 °C to produce carbon from lignin, as well as to investigate the effect of temperature. A higher pyrolysis temperature will produce a porous carbon with a high specific surface area, but it will lower the yield of the produced carbon. At 850 °C temperature, the highest surface area up to 974 m2/g was achieved.